Dominica : Joint Staff Assessment of the Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2004)
This paper provides the joint assessment of the staff of the World Bank and the IMF on the interim poverty reduction strategy paper (I-PRSP) prepared by the government of the Commonwealth of Dominica and submitted to the World Bank and the IMF. The preparation of this I-PRSP-the later full PRSP-is intended to provide a framework for assistance under the poverty reduction and growth facility. The authorities have consented to the publication of both the I-PRSP and the joint staff assessment (JSA).